Pengaruh Pembiayaan Ijarah, Musyarakah, Murabahah, Mudharabah Terhadap Profitabilitas Pada Bank Syariah Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022 - Farid Faradin; Ronny Malavia Mahardani; Nurhidayah Nurhidayah (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of ijarah, musyarakah, murabaha, mudharabah financing influences the profitability of case studies at Islamic banks listed on the Indonesia Stock Exchange for the 2020-2022 period. In this study there were 4 (four) independent variables namely ijarah, musyarakah, murabahah, mudharabah. And the dependent variable in this study is profitability which is calculated using the ratio of return on assets. The population and sample in this study are the financial statements of Islamic banks listed on the Indonesian Stock Exchange. The data collection method used is documentation with reference to the bank's quarterly financial reports. The data analysis technique used in this study is linear regression. The results of the study partially state that ijarah has a negative and insignificant effect on profitability. Musyarakah and mudharabah financing have a positive and insignificant effect on profitability. Murabaha financing has a negative and significant effect on profitability. Keywords: Ijarah, Musyarakah, Murabaha, Mudharabah, Profitability